Implementation Of The Pancasila Student Profile With The Dimension Of Faith, Fear Of Almighty God And Noble Character In Elementary Schools - Sulistyowarni, Putri; Prasetyo, Koko; Suswandari, Meidawati (Jurnal Mamangan, 2024)
Through the Strengthening Pancasila Profile Project, it is hoped that students will be able to internalize and apply Pancasila values in everyday life and form strong and morally and socially responsible personalities. The aim of this research is to describe the program for cultivating the character of faith, devotion to God Almighty and noble morals at SD Negeri Pondok 01. This research method uses qualitative research. Qualitative research is research that examines human or social phenomena naturally and comprehensively, based on data obtained from informant sources, and the results are presented in narrative form. The results of this research, with the habituation that has been carried out by students, has had a good positive impact in forming religious values and devotion to God Almighty at school. Even though the independent curriculum has not been fully implemented in all classes and the Pancasila student profile is still progressing gradually, evaluation of its implementation shows positive behavioral changes in students.